Aesthetic Alteration of the Chin - Lee, Edward I. (Seminars in Plastic Surgery, 2013)
Genioplasty, the alteration of the chin through either osseous manipulation or implant augmentation, is an integral component of aesthetic surgery of the face. When performed with proper preoperative assessment and technical execution, the results can harmonize and restore balance between skeletal, soft tissue, and dental components of the lower face. To this end, proper understanding of the underlying anatomy and the changes associated with movement of the chin, alone or in conjunction with formal orthognathic surgery, is paramount. The author presents pertinent points on proper assessment, treatment planning, and a description of the surgical technique, and discusses complications and outcomes to optimize outcome.
Keywords: genioplasty; osseous genioplasty; chin surgery; alloplastic chin augmentation